Twenty-Year Retrospective Study of Post-Enucleation Chemotherapy in High-Risk Patients with Unilateral Retinoblastoma - Yoon Sunwoo; Jung Yoon Choi; Hyun Jin Park; Bo Kyung Kim; Kyung Taek Hong; Sang In Khwarg; Jaemoon Koh; Sung-Hye Park; Dong Hyun Jo; Jeong Hun Kim; Jung-Eun Cheon; Hyoung Jin Kang (MDPI AG, 2022)
Primary enucleation is a life-saving treatment for advanced intraocular retinoblastoma, particularly in patients with poor visual potential and functional contralateral eyes. This single-center study presents the treatment outcomes of patients with unilateral retinoblastoma who received primary enucleation and adjuvant chemotherapy with cyclophosphamide, vincristine, doxorubicin, and intrathecal methotrexate (CVDM) between 2000 and 2020. Twenty patients were enrolled in the study. The median age at diagnosis was 26 months (range, 1-45). Eighteen patients (90%) were in group E and two (10%) were in group D, according to the intraocular classification of retinoblastoma guidelines. Excluding one patient with an inadequate specimen, 19 patients (95%) had optic nerve involvement (ONI) at least up to the lamina cribrosa. Eight patients (40%) had choroidal invasion in addition to ONI. Two patients (10%) were surgical resection margin positive. The overall and event-free survival rates were 100% and 95%, respectively, for a median follow-up duration of 102.24 months (range 24.2-202.9). There were no relapses or deaths due to any cause, but one patient developed secondary rhabdomyosarcoma 99.6 months after chemotherapy. Treatment was well tolerated, with minimal hematotoxicity and hepatotoxicity. CVDM as a post-enucleation chemotherapy for advanced intraocular retinoblastoma has excellent outcomes with tolerable toxicity. However, in line with updated treatment trends, further risk stratification and lowering the treatment intensity should be considered. Continued long-term follow-up is required to further determine late effects.